Coronavirus disease 2019 infection in patients with recent cardiac surgery: does chronic anticoagulant therapy have a protective effect?. Issue 10 (October 2020) - Inama, Giuseppe; Dodi, Claudio; Provini, Martino; Bossoni, Enzo; Inama, Lorenza; Balzarini, Laura; Mancini, Chiara; Ramponi, Sara; Marvisi, Maurizio
Abstract : Aims: The aim of this study was to evaluate the clinical course of COVID-19 in patients who had recently undergone a cardiac procedure and were inpatients in a cardiac rehabilitation department. Methods: All patients hospitalized from 1 February to 15 March 2020 were included in the study ( n = 35; 16 men; mean age 78 years). The overall population was divided into two groups: group 1 included 10 patients who presented with a clinical picture of COVID-19 infection and were isolated, and group 2 included 25 patients who were COVID-19-negative. In group 1, nine patients were on chronic oral anticoagulant therapy and one patient was on acetylsalicylic acid (ASA) and clopidogrel. A chest computed tomography scan revealed interstitial pneumonia in all 10 patients. Results: During hospitalization, COVID-19 patients received azithromycin and hydroxychloroquine in addition to their ongoing therapy. Only the patient on ASA with clopidogrel therapy was transferred to the ICU for mechanical ventilation because of worsening respiratory failure, and subsequently died from cardiorespiratory arrest. All other patients on chronic anticoagulant therapy recovered and were discharged. Conclusion: Our study suggests that COVID-19 patients on chronic anticoagulant therapy may have a more favorable and less complicated clinical course. Further prospective studies are warranted to confirm this preliminary observation.